In vivo infectivity of liver extracts after resolution of hepadnaviral infection following therapy associating DNA vaccine and cytokine genes. Issue 4 (26th December 2012) - Saade, F.; Buronfosse, T.; Guerret, S.; Pradat, P.; Chevallier, M.; Zoulim, F.; Jamard, C.; Cova, L.
Summary DNA‐based vaccination appears of promise for chronic hepatitis B immunotherapy, although there is an urgent need to increase its efficacy. In this preclinical study, we evaluated the therapeutic benefit of cytokine (IL‐2, IFN‐γ) genes co‐delivery with DNA vaccine targeting hepadnaviral proteins in the chronic duck hepatitis B virus (DHBV) infection model. Then, we investigated the persistence of replication‐competent virus in the livers of apparently resolved animals. DHBV carriers received four injections of plasmids encoding DHBV envelope and core alone or co‐delivered with duck IL‐2 (DuIL‐2) or duck IFN‐γ (DuIFN‐γ) plasmids. After long‐term (8 months) follow‐up, viral covalently closed circular (ccc) DNA was analysed in duck necropsy liver samples. Liver homogenates were also tested for in vivo infectivity in neonatal ducklings. Co‐delivery of DuIFN‐γ resulted in significantly lower mean viremia starting from week 21. Viral cccDNA was undetectable by conventional methods in the livers of 25% and 57% of animals co‐immunized with DuIL‐2 and DuIFN‐γ, respectively. Interestingly, inoculation of liver homogenates from 7 such apparently resolved animals, exhibiting cccDNA undetectable in Southern blotting and DHBV expression undetectable or restricted to few hepatocytes, revealed that three liver homogenates transmitted high‐titre viremia (3–5×1010 vge/mL) to naïve animals. In conclusion, our results indicate that IFN‐γ gene co‐delivery considerably enhances immunotherapeutic efficacy of DNA vaccine targeting hepadnaviral proteins. Importantly, we also showed that livers exhibiting only minute amounts of hepadnaviral cccDNA could induce extremely high‐titre infection, highlighting the caution that should be taken in occult hepatitis B patients to prevent HBV transmission in liver transplantation context.